1992
DOI: 10.1016/0035-9203(92)90161-5
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of human skeletal muscle sarcocystosis in south-east Asia

Abstract: The prevalence of human skeletal muscle sarcocystosis in Malaysia was determined by serial examination of formalin-fixed, paraffin-embedded sections of tongue tissues obtained from consecutive, routine autopsies of subjects aged 12 years or more. Of 100 tongues examined, 21% were found to contain Sarcocystis; 66 cysts were found. The number of cysts per case varied from 1 to 13. In one case, 5 cysts were found in a single tissue section. The age range of positive cases was from 16 to 57 years (mean 37.7 years)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
37
0
2

Year Published

1995
1995
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 6 publications
1
37
0
2
Order By: Relevance
“…8,12 Human muscle sarcocystosis is highly prevalent in Southeast Asia. Muscle tissue examinations in Malaysia were positive in 21% of 100 consecutive routine autopsy samples, 13 and 19.8% of a Malaysian population sample had serologic evidence of sarcocystosis exposure. 14 Although these infections have been considered to be incidental findings, some investigators have suggested that sarcocystosis may be emerging as a significant food-borne zoonosis in Southeast Asia.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…8,12 Human muscle sarcocystosis is highly prevalent in Southeast Asia. Muscle tissue examinations in Malaysia were positive in 21% of 100 consecutive routine autopsy samples, 13 and 19.8% of a Malaysian population sample had serologic evidence of sarcocystosis exposure. 14 Although these infections have been considered to be incidental findings, some investigators have suggested that sarcocystosis may be emerging as a significant food-borne zoonosis in Southeast Asia.…”
Section: Discussionmentioning
confidence: 98%
“…19 A growing body of evidence suggests that Sarcocystis muscle infection can be associated with significant disease. [1][2][3]5,[8][9][10][11][12][13][14][15][16] The high prevalence of muscle infection in indigenous Malaysian populations suggest that sarcocystosis is a common, seldom recognized infection in Malaysia. 11,15 As described above, other investigators have reported a spectrum of manifestations ranging from asymptomatic or acute, self-limited complaints to moderately severe, chronic illness.…”
Section: Discussionmentioning
confidence: 99%
“…A histopathologic study of tongue skeletal muscle found 21 of a series of 100 autopsy cases from a local urban population to be positive for sarcocysts. 9 In 1999, an outbreak of eosinophilic myositis attributed to skeletal muscle Sarcocystis spp. infection was reported and involved 7 of 15 U.S. military personnel who had operated in rural Malaysia.…”
mentioning
confidence: 99%
“…The outbreak has received attention due to the severity of disease and because the infected individuals were almost exclusively European tourists (5,6). Also supported by the prevalence studies in Malaysia (25,29), this indicates that the indigenous population is at substantial risk of contracting disease. In addition, an outbreak of muscular sarcocystosis was observed in 89 Malayan college students who visited Pangkor Island (38).…”
Section: Epidemiology and Clinical Significancementioning
confidence: 97%